Egy kis egyetemtörténet anekdotákban - Gaál, Botond (Gerundium, 2014)
THE HISTORY OF THE UNIVERSITY IN STORIES. he writing remembers the teachers of the Reformed heological Faculty of the Debrecen University in anecdotes. he work and academic activities of the cited professors are commemorated through interesting stories and funny anecdotes. he author describes these professors amicably and amusingly as nice people who seem sometimes rigorous or eccentric, and who strived to maintain the high quality of academic work.